Respostas

2014-07-01T02:24:08-03:00
O numerador, dentro da raiz, tem que ser maior ou igual a zero e o denominador, diferente de zero. Assim, p/ y = √(x-3)(x-1)/x, temos:
(x-3)(x-1) ≥ 0
x² - x -3x +3 ≥ 0
x² - 4x + 3 ≥ 0
Δ = (-4)² - 4(1)(3) = 16 - 12 = 4
x' ≥ [-(-4) + 2]/2 ≥ (4+2)/2 ≥ 3
x" ≥ [-(-4) - 2]/2 ≥ (4-2)/2 ≥ 1
...........
x ≠ 0
..........
a) x ≥ 1 ===>>> ----------------------1++++++++++++++++
b) x≥ 3 ===>>>  -------------------------------------3++++++++
c) x ≠ 0===>>> ++++++++0+++++++++++++++++++++
a)∩b)∩c)==>>  --------------0-------1-------------3++++++++
                                              D(y) = {x ∈ IR / x ≥ 3}
2 5 2